Chemical Constituents from the Stem Barks of Plumeria rubra L. - Surendra Kumar Sharma; Mohammed Ali*; Naresh Kumar; Shahnaz Sultana; Showkat Rasool Mir (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Plumeria rubra L. (Apocynaceae) is a deciduous shrub or small tree cultivated in subtropical and tropical countries.  Its bark is prescribed to treat amoebic dysentery,   dropsy, jaundice, scabies, gonorrhea, venereal affections and wounds. In the present research, we aimed to isolate and identify the chemical constituents of the bark of P.   rubra. Method: An air-dried bark powder of P. rubra was exhaustively extracted with methanol.  Methanol was removed afterwards under vacuum to get a dark brown mass. The extract was dissolved and adsorbed on silica gel (60-120 mesh) for preparation of slurry. The slurry was loaded over silica gel column packed in petroleum ether. The column was eluted with organic solvents successively in order of increasing polarity to isolate the chemical constituents. The structures of the phytoconstituents, isolated from the plant for the first time, have been elucidated by analyzing the spectral data and on the basis of chemical reactions. Results: Phytochemical investigation of a methanol extract of the stem bark led to isolate  n-octyl n-octadecanoate (n-octyl stearate, 1), lauryl-O-α-D-glucopyranosyl-(2ʹ→1ʹʹ)-O-β-D-glucopyranoside (lauryl diglucoside, 2), stearyl-α-L-xylopyranosyl-(2ʹ→1ʹʹ)-α-L-xlyopyranosyl-2ʹʹ-(3ʹʹ-oxy-4ʹʹʹ-hydroxy-5ʹʹʹ-methoxy)-benzoic acid (stearyl dixylosyl methoxygallic acid, 3), vanillic acid 4-O-β-D-arabinopyranosyl-(2a→1b)-O-β-D-arabinopyranosyl- (2b→1c)-O-β-D-arabino-pyranosyl-(2c→1d)-O-β-D-arabinopyranosyl-2d-stearate (vanillic acid 4-O-tetra-arabinosyl stearate, 4), vanillic acid 4-O- β-D-arabinopyranosyl-(2a→1b)-β-D-arabinopyranosyl-(2b→1c)-β-D-arabino- pyranosyl-(2c→1d)-β-D-arabinopyranosyl-(2d→1e)-β-D-arabinopyranosyl-(2e→1f)-β-D-arabino-pyranosyl-2f-stearate (vanillic acid 4-O-hexa-arabinosyl stearate, 5), β-D-glucopyranosyl-(2a→1b)-O-β-D-glucopyranosyl-(2b→1c)-O-β-D-glucopyranosyl- (2c→1d)-O-β-D- glucopyranosyl-(2d→1e)-O-β-D-glucopyranosyl-(2e→1f)-O-β-D- glucopyranoside (β-D-hexaglucoside , 6) and β-D-glucopyranosyl-(2a→1b)-O-β-D-glucopyranosyl-(2b→1c)-O-β-D- glucopyranosyl-(2c→1d)-O-β-D- glucopyranosyl-(2d→1e)-O-D- glucopyranosyl-(2e→1f)-O-β-D- glucopyranosyl-(2f→1g)-O-β-D-glucopyranosyl-(2g→1h)-O-β-D-rhamnopyranoside (β-D-heptaglucosyl-β-D-rhamnoside, 7). Conclusion: The stem bark of P.  rubra contained a variety of chemical constituents like  a fatty  ester, acyl  glycosides,  vanillic acid glycosides and polyglycosides.